Dynamics of the rise of the privately-run and government-subsidised think tank and its influence in talent policy making—case study of the Zhejiang Institution of Talent Development. Issue 1 (2nd January 2017) - Chen, Lijun; Fu, Yan
Abstract: Since China's reform and opening up, the role of think tanks in policy-making has increased providing decision-makers with an 'internal reference' for agenda setting. Think tanks are frequently entrusted by government to undertake policy research projects. In the context of strong ideological control where official think tanks have dominated, a new-type of privately-run and government-subsidised think tanks has emerged in the field of talent policy. Using the Zhejiang Institution of Talent Development as an example of a typical privately-run and government-subsidised think tank, this study explores the dynamics of the increasing role and influence of such think tanks in policy making. Firstly, at a macro level, there is increasing demand for skilled labour as China's economy grows and changes, and provinces compete for talent: this has led to increasing demand by provinces for talent policies and, given their limited policy-making expertise, to increasing dependence on external think tanks' policy research expertise. Then, the study describes ZITD's structure and operations, and analyses ZITD's 'participation mode' approach involving participation in four phases of policy development: preliminary research, agenda setting, program design, ultimate decision making. From this, the study concludes that the key success factors for privately-run and government-subsidised think tanks are: building long-term sustainable cooperation between government and experts, promoting evidence-based talent policy decision-making, and canvassing a wide range of possible policy objectives. Also, however, such think tanks face challenges in expressing independent opinions, recruiting and retaining their own experts and expanding their influence in decision-making. Finally, whether the rise of privately-run and government-subsidised think tanks improves public participation or democracy in policy-making system could be the subject of further exploration.